EFFECTIVENESS OF INTERVENTION PROGRAMS ON KNOWLEDGE AND ATTITUDE TOWARDS ORAL CANCER AMONG DENTAL PATIENTS: VIDEO VERSUS POSTER - Kotian, Santhosh; Mohamad Hanapi, Nur Sulwana; Chong , Li Ang; Neo , Temmeera; Binti Hashim, Sofea Nur’ Aleena (Malaysian Journal of Public Health Medicine, 2024)
Oral cancer survival rate is higher when it is detected during the early stages. But the lack of adequate knowledge and awareness among the people has made early detection a challenging process. This study aims to identify and compare the effectiveness of intervention programs such as video and poster, on improving the knowledge and attitude of dental patients towards oral cancer. 116 dental patients were divided into two groups. After answering the questionnaire before the intervention, oral cancer awareness was provided for one group using a poster and to the other group using a video with similar contents. The Part B (knowledge) and Part D (attitude) of the questionnaire was answered by the participants post-intervention. The pre- and post-intervention responses of the participants were noted and statistically analysed within and between the groups at p=0.05. Statistically significant increase in the number of correct responses to most of the questions in Part B was seen in both poster and video groups. Whereas improved responses for only 2 questions in the poster group were found to be statistically significant against the video group. Statistically significant increase in the post-intervention scores of Part D were seen in both groups. Hence, both video and poster intervention groups were found to be equally effective in improving the knowledge and attitude of the participants towards oral cancer. Poster intervention was found to be comparatively more effective in improving correct responses to some items related to knowledge on signs and symptoms of oral cancer.